Migrating Modernist Interiors - Mia Åkerfelt; Anna Wilczynska; Tzafrir Fainholtz; Martti Veldi (Docomomo Journal)
After World War II, Finland and Poland needed swift housing reconstruction. In Finland, the solution was prefabricated, wooden detached houses, which soon were exported globally. In 1947-48, Poland imported around 4,000 Finnish houses to the mining areas in Silesia. The architecture was based on domestic Finnish models developed from modernist housing ideals. The division of the interiors focused on rational usage of space, labor, and hygiene. Today, most of the buildings are preserved, and it is possible to track the adaptations of the architecture from foreign temporary structures to local homes and heritage to provide data for developing future reconstruction architecture. This article analyzes how Finnish modernist ideals on home and housing were circulated internationally by exporting prefabricated wooden housing to reconstruction areas in Upper Silesia. The main questions relate to how the Finnish ideology on modernist housing and interior planning was adapted to the local culture of home and housing in Silesia and what can be learned from the reception and adaption of the interiors when designing housing for reconstruction after crises today. The article is based on archival material from Finland and Poland, such as architectural drawings, maps, and documentation on trade and export. The main methodologies are architectural and design analysis combined with historiographic reading of archival data and literature. The article shows how architecture with interiors planned for Finnish domestic use became integrated into the Silesian home culture, transforming temporary housing into permanent homes.